2015
DOI: 10.1097/yco.0000000000000139
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in testing social cognition

Abstract: In the past 20 years, research on social cognitive function has grown exponentially, reflecting an increased recognition that social cognitive skills are critical for communicative discourse, and in turn mental health and well-being. Accordingly, a large number of measures are now available to quantify social cognitive function. This review shows that many of these measures have good psychometric properties, and appear to have at least moderate sensitivity. However, the review also highlights the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 30 publications
2
52
0
Order By: Relevance
“…While it has been shown that several social cognitive tasks, especially assessments of ToM, have high test-retest or interrater reliability [see, e.g., (152)], the extent to which impairments on the various social cognitive tasks that OCD patients exhibit are valid indications of social cognitive problems in daily life is currently unclear. Notably, effect sizes for disgust recognition deficits in OCD patients were much smaller for tasks employing morphed compared to static facial expressions (41), whereas the first can be seen as the most ecologically valid and subtle assessment of emotion recognition.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been shown that several social cognitive tasks, especially assessments of ToM, have high test-retest or interrater reliability [see, e.g., (152)], the extent to which impairments on the various social cognitive tasks that OCD patients exhibit are valid indications of social cognitive problems in daily life is currently unclear. Notably, effect sizes for disgust recognition deficits in OCD patients were much smaller for tasks employing morphed compared to static facial expressions (41), whereas the first can be seen as the most ecologically valid and subtle assessment of emotion recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions on eloquence of the cerebellum for social cognition would benefit from sufficiently powered studies in patients with rather homogeneous lesion size, topography and etiology at defined time-points after disease onset. In addition, consideration of ecological validity appears helpful when assessing impact on everyday social function (Henry et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that cognitive training has a positive effect on cognitive function, and the preservation of cognitive function is associated with a healthier lifestyle and greater well-being (Henry et al, 2015; Llewellyn et al, 2008; WHO, 2011). However, recent studies on computer-based cognitive training have focused mainly on improvements in cognitive function or transfer to other cognitive tasks (Kueider et al, 2012; Maseda et al, 2013; Rizkalla, 2015; Shatil et al, 2014; Van Muijden, Band & Hommel, 2012) rather than on the self-perceived emotional experience denoted as well-being.…”
Section: Introductionmentioning
confidence: 99%